Singapore: Building a future without cheap oil - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2011)
Singapore’s past success at building a world-class economy launched on the back of a hugely successful oil refining and trading system could count for little as it confronts the threats of the increasing scarcity and cost of energy supply. In a book commissioned by the International Trading Institute@SMU, 'Singapore, The Energy Economy: From The First Refinery To The End Of Cheap Oil, 1960 to 2010', author Ng Weng Hoong argues that Singapore’s single-minded focus on growing the economy while assuming that the supply of energy and natural resources will always be cheap and plentiful leaves the city-state increasingly vulnerable and dangerously exposed to systemic shocks and even collapse.